The effect of education through a mobile application on self-care behavior in patients undergoing percutaneous coronary: A randomized clinical trial - Khatereh Salavati; Nahid Rejeh; Farhad Rohani; Alireza Dehghan Nayeri (Tehran University of Medical Sciences, 2024)
Background & Aim: Patients who receive percutaneous coronary interventions often display inadequate levels of self-care actions, which could create difficulties in managing the disease and achieving favorable treatment results. This study investigates the impact of using an educational mobile application on self-care behaviors in patients undergoing percutaneous coronary intervention. Methods & Materials:  A randomized clinical trial was conducted with 110 patients undergoing percutaneous coronary interventions at Shahid Rajaei Hospital in Karaj, Iran, in 2023. The study enrolled and assigned them to either the intervention group (n=55) or the control group (n=55) by block randomization. In addition to training upon discharge, the experimental group received educational resources via a mobile phone application. The data collection instruments included MSCBS. Patients completed the MSCBS before the intervention and 4 weeks later. The data were analyzed with SPSS 21. The study's level of significance was set to P<0.05. Results: Before the intervention, there was no significant difference in the self-care scores and the subscales between the two groups (P<0.05). Nonetheless, After the intervention, a significant difference was observed in the self-care scores and the subscales between the control and intervention groups, (p=0.001), and the difference in scores between the control and intervention groups increased significantly after the intervention and the scores of the intervention group had a significant increase compared to the scores of the control group. Conclusion: The study showed that the mobile phone educational application could improve self-care behaviors in patients undergoing percutaneous coronary interventions. Therefore, it can be recommended that nurses working in medical centers use this educational application to enhance self-care in these patients.